Do Exclusionary Rules Ensure a Fair Trial? : a Comparative Perspective on Evidentiary Rules - Gless, Sabine; Richter, Thomas (Springer International Publishing : Imprint : Springer, 2019)
This open access publication discusses exclusionary rules in different criminal justice systems. It is based on the findings of a research project in comparative law with a focus on the question of whether or not a fair trial can be secured through evidence exclusion. Part I explains the legal framework in which exclusionary rules function in six legal systems: Germany, Switzerland, People's Republic of China, Taiwan, Singapore, and the United States. Part II is dedicated to selected issues identified as crucial for the assessment of exclusionary rules. These chapters highlight the delicate balance of interests required in the exclusion of potentially relevant information from a criminal trial and discusses possible approaches to alleviate the legal hurdles involved.
Keywords: Criminal law.; Criminal justice, Administration of.; Social justice.; Justice sociale.